Mathematical Modeling of Linear Momentum to determine The Breaking Pattern of Coal Physical Collision - Fahrizal; Lukman Hakim Nasution; Yoan Purbolingga; Dila Marta Putri; Asde Rahmawati; Bastul Wajhi Akramunnas (Fakultas Teknik Universitas Pasir Pengaraian, 2023)
A study shows that 40% of steam power plants in Indonesia use coal as a fuel in boiler systems. The number of power plants using coal is increasing; in 2030, it is estimated to produce 4,500 GW of electricity. The coal fuel for the combustion process should be in powder form in order to produce a complete combustion. Generally, a crusher is used to produce coal chunks, and then a grinder is needed to bring the chunks to powder form. By using a linear momentum mathematical model, the coal breaking pattern can be predicted. From this study, the state of coal throughout the transformation process could be classified into 3 stages; initial state, static impact and momentum effect. The above studies would influence the mathematical modeling of the breaking pattern, and the transformation process in coal physical collision. Therefore, to produce coal in the form of powder can be carried out with an impact system, not only a system of grinding such as in the grinding process.